2022
DOI: 10.1021/acsomega.2c03534
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Interacts with α-Synuclein Condensates To Inhibit Amyloid Aggregation under Phase Separation

Abstract: The amyloid aggregation of α-synuclein (α-Syn) is highly associated with Parkinson’s disease (PD). Discovering α-Syn amyloid inhibitors is one of the strategies for PD therapies. Recent studies suggested that α-Syn undergoes phase separation to accelerate amyloid aggregation. Molecules modulating α-Syn phase separation or transition have the potential to regulate amyloid aggregation. Here, we discovered that curcumin, a small natural molecule, interacts with α-Syn during phase separation. Our study showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…The anti-amyloidogenic properties of polyphenols may also benefit Parkinson’s neurodegeneration, since the deposition of Lewy bodies, consisting of a large part of α-synuclein aggregates, in neuron cytoplasm is a key pathological PD hallmark [ 126 ]. In fact, the progressive degeneration of dopaminergic neurons of the substantia nigra pars compacta, together with iron accumulation, provides dopamine depletion in the striatum, thus neuromelanin disappear and Lewy bodies become visible.…”
Section: Polyphenols Vs Neurodegenerative Diseasementioning
confidence: 99%
“…The anti-amyloidogenic properties of polyphenols may also benefit Parkinson’s neurodegeneration, since the deposition of Lewy bodies, consisting of a large part of α-synuclein aggregates, in neuron cytoplasm is a key pathological PD hallmark [ 126 ]. In fact, the progressive degeneration of dopaminergic neurons of the substantia nigra pars compacta, together with iron accumulation, provides dopamine depletion in the striatum, thus neuromelanin disappear and Lewy bodies become visible.…”
Section: Polyphenols Vs Neurodegenerative Diseasementioning
confidence: 99%
“…It is worth mentioning that some polyphenols, such as myricetin and curcumin, have been recently described to inhibit α-Syn liquid-to-solid transition in LLPS condensates. Adding these polyphenols to the condensates did not impact their morphology, but they increased the protein solubility, preventing amyloid transition and disentangling the preformed aggregates [ 253 , 254 ]. Structure–Activity Relationship (SAR) analysis of multiple phenolic variants with inhibitory activity revealed that the phenyl group alone does not prevent fibril formation [ 255 ].…”
Section: New Therapies: Modulating α-Synuclein Aggregationmentioning
confidence: 99%
“…This interaction with condensates reduces the diffusion of the protein, which ensures the inhibition of the formation of aggregates. Curcumin has also been shown to inhibit not only wild-type (WT) amyloids, but also α-synuclein mutant E46K and H50Q amyloids in condensates, making it a potential treatment for PD [ 139 ]. In addition to the above, there is an alternative hypothesis about the mechanism of inhibition of amyloid aggregation, which consists of inhibiting the generation of oxidative stress, increasing reduced glutathione, and preventing a glial-associated inflammatory response [ 140 ].…”
Section: Influence Of Various Molecules On the Aggregation Processmentioning
confidence: 99%